KARAKTERISTIK FISIKOKIMIA DAN SENSORI MANISAN TOMAT (Lycopersicum esculentum) - Finarsih Tendean; Lana E. Lalujan; G.S. Suhartati Djarkasi (Universitas Sam Ratulangi, 2016)
ABSTRACTCandied tomato is a tomato processing alternatives that can be done to take advantage of tomatoes were very susceptible to damage after harvest and are often consumed in fresh form. The purpose of this study to determine the effect of the addition of sugar to the physicochemical characteristics of candied tomatoes and measure the level of a panelists against to candied tomatoes. The research arranged using Factorial Completely Randomized Design with the addition of sugar multilevel treatment. Results of research for the candied tomato water content ranged from 18.45 to 30.94 % . The water content is highest in treatment A2 is the addition of sugar 40 % , while the water content was lowest for the treatment A3 is the addition of sugar to 50% with the drying temperature used in all treatments, 550C. The results of the analysis of sucrose concentration ranged from 44.81 to 70.80 % . Sucrose concentration is highest in the treatment of A4 is the addition of sugar to 60% with an average of 70.80 % , while the sucrose concentration was lowest for the treatment A1 is the addition of sugar to 30% with an average of 44.81 %. The results of the analysis of vitamin C for four treatments ranged from 2.78 to 4.08 mg / 100gr . Texture analysis for the four treatments ranged from 2.8 to 4.1 kg/cm2 . Sensory testing candied tomatoes with parameters of taste , color and aroma is the preferred sample A3 is the addition of sugar 50 % .Keywords : candied tomatoes , physicochemical and sensory properties